Concepções sobre ser menino e ser menina de uma turma de crianças de multi-idade na educação infantil - Machado, Angelita Maria (2023)
This research is part of Research Line LP2 - Educational Public Policies, Educational Practices and their Interfaces, of the Postgraduate Program in Education at the Federal University of Santa Maria. The research problem was: how to problematize with children the conceptions about being a boy and being a girl in society through children's literature? As a general objective, the aim was to: understand the meanings constructed by children about the ways of being a boy and being a girl, existing between characters in some children's literature stories. And as specific objectives: a) analyze the conceptions about being a boy and being a girl, constructed and expressed by children in a multi-age early childhood education class, considering gender and childhood studies; b) understand the role of Children's Literature as a cultural artifact that enables the construction of meanings about the world; c) analyze how Children's Literature interferes in the construction of conceptions of gender, more specifically, related to the ways of being a boy and being a girl. The methodology used a qualitative, ethnographic, social constructionist approach and research with children, since, in addition to observation and recording, interventions were carried out with children aged between 3 and 5 years and 11 months through children's literature books. The research context was a Federal Public School in Santa Maria. For the theoretical foundation, authors such as Vianna; Finco (2009); Salva and Vinholes (2014); Moysés Kuhlmann (2000); Bujes (2001); Faria and Salles (2007); Corsaro (2009); Lajolo (2010); Sarmento (2007); Louro (2019). The concept of gender, in this research, is understood as a social construction in which it is directed to behaviors and attitudes expected by boys and girls. The study showed the complexity of working with children of different ages using children's literature as an artifact. Some older children expressed aspects related to gender that were already naturalized by society, but not without questioning from other children. Through drawing, it was not possible to perceive marks of the children's meanings, perhaps because the school does not have a practice of using drawing linked to storytelling. And even though counter-hegemonic children's literature has been read and discussed explicitly, at this moment, the meanings seem to correspond to the marks left historically in our society. It is also clear how much there is a need for continued training for teachers on Children's Literature as a cultural artifact and how much government book distribution programs are missing in schools